2014
DOI: 10.4172/2375-4508.1000148
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease, Infertility Treatment and In Vitro Fertilization (IVF)

Abstract: Periodontal disease and particularly periodontitis is a chronic bacterial infection, and belongs, as well as various other acute or subclinical infections, especially of the urogenital system, appendicitis and AbstractIn the last years, research interest has focused on the possible role of maternal periodontitis in the achievement of a pregnancy, as well as the possible role of paternal periodontitis in the success of medication administered for the treatment of infertility. The purpose of this publication is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…14 Previous reports have also exhibited that PDs are associated with significant higher percentage of endometriosis 15 and maternal PDs can affect the effectiveness of infertility therapies and in vitro fertilization success. 16 Reportedly, PDs can also increase a woman's time to conception. 17 In general, since PDs may increase the risk of perinatal mortality and developmental disorders as well as infertility treatments failure (Figure 1), oral health promotions through well-organized strategies including regular preventive dental check-ups as well as lifestyle modifications should be prioritized particularly in mothers-to-be.…”
Section: Mini Reviewmentioning
confidence: 99%
“…14 Previous reports have also exhibited that PDs are associated with significant higher percentage of endometriosis 15 and maternal PDs can affect the effectiveness of infertility therapies and in vitro fertilization success. 16 Reportedly, PDs can also increase a woman's time to conception. 17 In general, since PDs may increase the risk of perinatal mortality and developmental disorders as well as infertility treatments failure (Figure 1), oral health promotions through well-organized strategies including regular preventive dental check-ups as well as lifestyle modifications should be prioritized particularly in mothers-to-be.…”
Section: Mini Reviewmentioning
confidence: 99%
“…Although a number of causes have been stated; the complex interplay between sex hormones and periodontal tissue still intrigues the scientific community. Very few studies have been carried out to understand the interaction of CC and gonadal hormonal supplements used to treat infertility and gingival/ periodontal tissue [11].…”
Section: Relationship To Periodontiummentioning
confidence: 99%
“…Ovulation induction is done using drugs like clomiphine citrate (cc) and gonadotropin such as follicle stimulating hormone (FSH), Human menopausal gonadotropin (HCG) etc. [11]. Hormones are signaling chemicals that are carried to distant organs in the body by the blood stream and have diverse effects on them.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic spread of bacterial products, components, and immune complexes is facilitated by the anatomic closeness of these microflora to the blood stream, which can cause systemic bacteremia. Recently, it has been identified that the maternal bacteremia caused by periodontal focus of infection can hamper not only the fetus but also the in the achievement of a pregnancy, primarily due to endotoxins and bacterial products in the blood circulation which cause bacteremia in the uterus [4].…”
Section: The Focal Theorymentioning
confidence: 99%
“…A significant failure rate in the various methods applied to treat infertility even today, despite the progress of knowledge and techniques being used, has recently triggered further research regarding other parameters of health including periodontal health in the achievement of pregnancy. However, it is only in the last couple of years that scientists have focused their interest on the effect of periodontal disease and the bacteremia it causes on the achievement of pregnancy either normally, or assisted by medications for infertility, or through the use of IVF (in vitro fertilization) [4]. Even though there are only a limited number of studies available on the connection between poor periodontal health and infertility, in both the sexes more extensive research is required to understand this correlation better; this article reviews the data, knowledge, and the few studies available on the said topic.…”
Section: Introductionmentioning
confidence: 99%